INVESTIGATING PRE-SERVICE TEACHERS' CLASSROOM MANAGEMENT PRACTICE IN A BILINGUAL CLASS - Dwiniasih Dwiniasih; Farah Sukmawati Wahidah; Susanto Susanto (Universitas Islam Negeri Alauddin Makassar, 2020)
For the decades, managing classroom becomes one of the most important topics as the concern to be developed by educational department in improving students' quality. One of them is preparing pre-service teachers by strengthening their teaching skills such as managing classroom. Therefore, this study aims to investigate pre-service teacher's classroom management and its problem faced, where observation checklist is used by other participants in reviewing forty respondents’ teaching performance. Meanwhile in supporting the second purpose; Interview is used to delve more the problem faced by pre-service teacher while managing classroom. The results reveal that the skill which is still not optimal related to the creation and maintenance of optimal learning conditions is the skill that shows response attitude because of nervous and tend to focus to the certain group or students considered comfortable. Meanwhile, skills related to the control of optimal learning conditions that is still not done optimally by the participants, namely finding and overcoming behavior that poses problems with the way of exile caused by frightened by pre-service teachers against increasingly poor or rebellious student responses. However, referring to overall indicator of classroom management skills, pre-service teacher could be categorized as having done a grade managing skills well.